Habitat between density and urban growth: The urban living in the Asian Megacities - Silvia Covarino (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Urban growth and urban population are the most important issues to consider for sustainable planning and urban design for this century. The problem requires a general understanding on the global scale, considering rapid urbanization as a result of the dynamics of immigration from rural to urban areas. Since the 1950s, cities never seized to grow and we are living not in the city or in a metropolitan area, but in mega-urban areas or megacities, where the population is more than tens of millions of people. In the contemporary urban environment, more than half of the entire population live in Urban areas, which can be considered an urban explosion. The research and the studies focus on Asian Cities because of their importance. Their unique context and vast area are interesting assets to understand the network in between and the future balance with the rest of the planet. On the vision of the next urban future, if we are looking at the map of the megacities in 2030, 2050 and 2100, high concentration, large urban areas and high population density will be in that region.